“AGREEMENTS”, “DECISIONS” AND “CONCERTED PRACTICES”: KEY CONCEPTS IN THE ANALYSIS OF ANTICOMPETITIVE AGREEMENTS - CRISTINA CUCU (Challenges of the Knowledge Society)
In their economic activity, undertakings conclude many agreements between them. But agreements between undertakings which can distort the competition -anticompetitive agreements- are prohibited. The Romanian and EU law prohibit “all agreements between undertakings, decisions by associations of undertakings and concerted practices which have as their object or effect the prevention, restriction or distortion of competition”. However, the terms ”agreements”, ”decisions” or ”concerted practices” are nowhere defined in the EU Treaties or in the Romanian law. These terms are key concepts in the analysis of anticompetitive agreements which can distort the competition. In the lack of a legal definition, these concepts have generated a complex body of jurisprudence, which has to be identified. The analysis of these key concepts necessarily entails the conceptual delimitation of the notions. On this purpose, the relevant legal provisions will be identified in the Romanian and EU law, as well as the decisions of the European Court of Justice in this matter. The present paper intends to present the conceptual evolution of the analysed notions, paying special attention to concerted practices and to parallel behaviour in price fixing on the market.